Analisis Faktor yang mempengaruhi Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Flourien Ch; Zahratunnissa Ulya (Jurnal Ekonomi, 2017)
This study aims to determine the effect of liquidity position, leverage, profitability, and firm size against dividend policy. Dependent variable in this research is dividend policy measured by dividend payout ratio. Independent variables used are the position of liquidity, leverage, profitability, and company size. This research is an associative research with a causal approach. The population of this research is a manufacturing company listed in Indonesia Stock Exchange (BEI) in 2012 until 2014. Samples determined by purposive sampling method, with the number of samples of 28 manufacturing companies so that the total observation in this study as much as 84 observations. The data used in this research is secondary data. Data collection techniques using documentation method through IDX official website: www.idx.co.id.Metode data analysis used is multiple linear regression analysis with the help of software SPSS for Windows 22.Result research proves that the liquidity position does not affect the dividend policy on the company manufacturing listed on the Indonesia Stock Exchange (BEI) for the period 2012-2014. Profitability and firm size have a positive effect on dividend policy on manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2012-2014, and leverage negatively affect dividend policy on manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2012-2014.